2021
DOI: 10.1007/s10865-021-00255-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of physical activity behavior change based on the current stage of change—an analysis of young people from Hawai’i

Abstract: This study investigated the corresponding change between psycho-social predictors and physical activity (PA) behavior and if these relationships were dependent on the stages of change from the Transtheoretical Model in Minority American adolescents. We conducted a longitudinal field study with N = 357 students aged 13–18 years (M = 14.24 years, SD = 0.88); predominantly Filipino (61.2%) using a test–retest design assessing psycho-social PA predictors (enjoyment, self-efficacy, family support, friends’ support,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 49 publications
0
7
0
9
Order By: Relevance
“…Furthermore, 19.1% of students with high levels of parental support met the PA recommendations. Similarly, Engels et al [ 36 ] found a positive and significant correlation between MVPA time and family support. Haidar et al [ 35 ] also found a positive and significant relationship between parental support and moderate PA, as well as with vigorous PA.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, 19.1% of students with high levels of parental support met the PA recommendations. Similarly, Engels et al [ 36 ] found a positive and significant correlation between MVPA time and family support. Haidar et al [ 35 ] also found a positive and significant relationship between parental support and moderate PA, as well as with vigorous PA.…”
Section: Discussionmentioning
confidence: 82%
“…Studies by De Bourdeaudhuij et al [ 33 ] and Zamarripa et al [ 43 ] have shown that decisional balance is a medium-to-large factor of effect for behavioral change in PA in children and adolescents. Several studies [ 23 , 25 , 32 , 44 , 45 ] have shown that there are stage differences in self-efficacy, positive benefits, and negative barriers, with self-efficacy and positive benefits increasing from the precontemplation to maintenance stages and negative obstacles decreasing. Numerous studies [ 22 , 29 , 34 , 36 , 41 ] have found that there are stage differences in both self-efficacy and decisional balance and that self-efficacy and positive benefits are medium to large effects and negative obstacles are medium-to-small effects.…”
Section: Resultsmentioning
confidence: 99%
“…This will help construct a factor set to better understand the pathways associated with the intervention and expand the theoretical framework of TTM. Related studies have demonstrated medium-to-large effects of exercise attitudes [ 33 ], exercise interests [ 41 , 45 ], exercise motivation [ 25 , 38 , 44 , 46 ], perceptual physical environment support [ 25 , 41 ], perceptual social support [ 33 , 41 , 45 ], and physical self-concept [ 38 , 41 , 42 ] in the PA stage transition. Furthermore, Engels et al [ 45 ] show that there are no stage differences in exercise knowledge, a view that appears to be contrary to common sense and needs to be further tested.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Wang et al [ 54 ] showed that higher levels of family support in Chinese adolescents were less likely to have insufficient PA. Engels et al [ 55 ] found a positive relationship between friends’ support and MVPA in Hawaiian adolescents. Furthermore, in the case of family support, the relationship was significant.…”
Section: Discussionmentioning
confidence: 99%